Republic of Kazakhstan : 2017 Article IV Consultation- Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights growth in Kazakhstan expected to strengthen to 2.5 percent in 2017 after a slowdown in 2016, reflecting higher oil production and the effect of substantial fiscal stimulus spending. The sharp exchange rate depreciation in late 2015 and early 2016 triggered a surge in consumer prices, but inflation has come down to levels consistent with the National Bank of Kazakhstan's target range. The medium-term outlook has improved; growth in the non-oil sector is expected to pick up gradually to 4 percent, benefiting from structural reforms and a resumption of bank lending. Uncertainty is high, however, because the economy remains vulnerable to commodity price swings and especially to a sustained decline in oil prices.